Viroid infection of citrus in Central India - Y. S. AHLAWAT; P. RAMACHANDRAN, D.K. GHOSH, S. MATHUR, K. N. GUPTA (Indian Phytopathology, 2002)
A survey of citrus orchards in certain parts of Central India revealed the presence of characteristic symptoms of bark scaling and leaf yellowing on Nagpur mandarin and mosambi grafted on Rangpur lime and rough lemon rootstock. Samples were collected from field and grafted on Etrog citron indicator plants. Nucleic acid extracted from bark tissue of field trees were also ana lysed by return polyacrylamide gel electrophoresis (R-PAGE). Results of both biological and R-PAGE analysis showed viroid infection in citrus orchards in this region.